MENINGKAT HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI RUPA MEMBUAT POSTER MELALUI STRATEGI 3M (MELIHAT, MENGOLAH DAN MENGEMBANGKAN) PADA ANAK BAKAT ISTIMEWA - Anisa Dwi Utami Marpaung; Fitriza Yunisa; Nabila Amelia; Nur Izzati; Nurhastuti (JURNAL JUDIKHU, 2023)
The purpose of this research is to be able to see student learning outcomes in the process of learning art to make posters through the 3M (Seeing, Processing and Developing) strategy for special talent children. The method used in this research is the SSR (Single Subject Research) method. And the data collection technique in this study is observation with four steps, namely planning, implementing, observing, and assessing and reflecting on learning activities. After doing all the steps one by one, the results showed that using the 3M method carried out in art teaching practice can increase student creativity in making posters for special talent children. Keyword : Gifted Children, Posters, Fine Arts, Learning Outcomes